PENGARUH PENGGUNAAN MODEL PROJECT BASED LEARNING (PBL)TERHADAP KETERAMPILAN METAKOGNITIF DALAM PEMBELAJARAN SEJARAH SISWA KELAS X FARMASI - Fitriya Anggarani; Bobi Hidayat (Swarnadwipa, 2019)
The purpose of the study was to determine the effect of using the Project Based Learning (PBL) model on the metacognitive skills of students of Pharmacy X class at SMK Muhammadiyah 3 Metro. This research method is quantitative research (quasi experiment) or quasi-experimental. Before the implementation of Project Based Learning (PBL) learning models in the classroom, there was a problem in students who were in the process of learning while only a portion of the students paid attention to the explanation of the material presented by the teacher in the history learning process, especially in class X Pharmacy In conducting research that is research preparation, test trials, pre-test treatment, learning activities and giving a test post. The results of the study are proven by the difference in the results of the test post scores between the classes given the treatment model of learning with the classes not given the Project Basead Learning (PBL) learning model. In addition to the results of the test post as for the difference in theaverage value obtained by the two different classes between the classes given thelearning model and the classes that were not given treatment of the Project Basead Learning (PBl) learning model. So it can be concluded that there is a significant effect for the application of the learning model in the process of learning history.